2018
DOI: 10.1142/s2575900018300023
|View full text |Cite
|
Sign up to set email alerts
|

Chinese herbal formulas for postmenopausal osteoporosis: A review of preclinical evidence on animal studies and molecular mechanism

Abstract: Whether Chinese herbal formulas are effective in treatment of postmenopausal osteoporosis remains unclear. The aim of this study is to explore the experimental evidence of both in vitro and in vivo preclinical studies using Chinese herbal formulas in postmenopausal osteoporosis. Searches were applied to various databases with relevant keywords. Original in vivo and in vitro studies using Chinese herbal formulas to treat postmenopausal osteoporosis, and with full text available, were included. Er-Xian Decoction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Study of apoptosis markers was also conducted to test our hypothesis. Expression profile of caspase 3, cytochrome C as an indicator of apoptosis has been reported earlier [ [56] , [57] , [58] ]. Downregulation of gene expression of cytochrome C and caspase 3 observed in the present study, suggests LG suppresses the expression of these apoptotic markers.…”
Section: Discussionmentioning
confidence: 73%
“…Study of apoptosis markers was also conducted to test our hypothesis. Expression profile of caspase 3, cytochrome C as an indicator of apoptosis has been reported earlier [ [56] , [57] , [58] ]. Downregulation of gene expression of cytochrome C and caspase 3 observed in the present study, suggests LG suppresses the expression of these apoptotic markers.…”
Section: Discussionmentioning
confidence: 73%
“…applied paeoniflorin to intervene osteoclast model differentiated from RAW 264.7 cell line to observe the effect of paeoniflorin on the osteoclast signaling pathway. The results suggested that paeoniflorin weakened the phosphorylation level of p65 NF-κB, that is, inhibited the activation of the NF-κB signaling pathway ( 115 , 116 ). The NF-κB pathway is one of the main biological pathways of osteoclast differentiation ( 117 ).…”
Section: Synergistic Effect Of Polyphenols and Gm To Treat Opmentioning
confidence: 99%
“…Both peony and snake seeds are traditional Chinese medicine and contain polyphenols. By inhibiting the NF-κB signaling pathway, the production of osteoclasts is inhibited, to achieve the therapeutic effect of osteoporosis ( 116 ) Figure 3 .…”
Section: Synergistic Effect Of Polyphenols and Gm To Treat Opmentioning
confidence: 99%